Evaluation of intubation condition following administration of rocuronium in comparison to atracurium in paediatric patients (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background. Optimum intubation condition is paramount important for early and easy passage of endotracheal tube through the glottis and that results from adequate muscle relaxation. Rocuronium and atracurium are muscle relaxants used for short and intermediate duration of surgical processes. Objective: This study, compares the intubation condition and haemodynamic changes in paediatric patients following administration of rocuronium and atracurium to get rid of the side effects of succinylcholine. Method. The study was carried out in 60 patients aged 11/2 to 10 years, ASA I-II, under general anaesthesia. The patients were divided into two groups: rocuronium Gr R and atracurium Gr A. Induction was done with halothane 3.5-4% and for intubation rocuronium 0.6 mg/kg and atracurium 0.46 mg/kg were given to patients of Gr R and Gr A respectively. The intubation condition was assessed and gradded at 60 seconds after neuromuscular blocking agents. At the same time TOF ratios were recorded. Results. Rocuronium produced good to excellent intubation condition (score 3.80 ± 0.07) in all patients at 60 seconds whereas that of atracurium poor intubation condition (score 2 ± 0.00). TOF ratios showed more relaxation of adductor pollicis muscle in Gr R than Gr A (Gr R = 60.43 ± 0.87, Gr A = 78.90 ± 0.72). (p < 0.001). Cardiovascular stability was not significantly difference in both the groups before induction and intubation. Conclusion. Rocuronium produced better intubation condition in comparison to atracurium. DOI: http://dx.doi.org/10.3329/jbsa.v23i1.18150 Journal of BSA, 2010; 23(1): 3-7